2017
DOI: 10.1021/acs.jmedchem.7b00875
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonium as a Surrogate for Ammonium: A New α7 Nicotinic Acetylcholine Receptor Partial Agonist with Desensitizing Activity

Abstract: Weak partial agonists that promote a desensitized state of the α7 nicotinic acetylcholine receptor (nAChR) have been associated with anti-inflammatory effects. Exemplar compounds feature a tertiary or quaternary ammonium group. We report the synthesis, structure, and electrophysiological evaluation of 1-ethyl-4-phenylthiomorpholin-1-ium triflate, a weak partial agonist with a sulfonium isostere of the ammonium pharmacophore. These results offer new insights in understanding nAChR-ligand interactions and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The diEPP family of a7 ligands were originally designed based on the nonselective orthosteric ganglionic nAChR agonist dimethylphenylpiperazinium, and they have been shown to act as a7 antagonists, partial agonists, and silent agonists depending on the substitution of the phenyl ring or the nature of the charged group (Quadri et al, 2016(Quadri et al, , 2017Horenstein and Papke, 2017). In the present work, we identified the allosteric agonism of a diEPP derivative, 2NDEP, formerly reported as a weak partial agonist of a7 nAChR.…”
Section: Discussionmentioning
confidence: 85%
“…The diEPP family of a7 ligands were originally designed based on the nonselective orthosteric ganglionic nAChR agonist dimethylphenylpiperazinium, and they have been shown to act as a7 antagonists, partial agonists, and silent agonists depending on the substitution of the phenyl ring or the nature of the charged group (Quadri et al, 2016(Quadri et al, , 2017Horenstein and Papke, 2017). In the present work, we identified the allosteric agonism of a diEPP derivative, 2NDEP, formerly reported as a weak partial agonist of a7 nAChR.…”
Section: Discussionmentioning
confidence: 85%
“…Different silent compounds (Fig. 1B) such as NS-6740 ( 14 ) [38], KC-1 ( 15 ) [36], ASM-024 ( 16 ) [39], diEPP ( 17 ) [40], p -CF 3 -diEPP ( 18 ) [41], the sulfonium salt 19 [42], and the spirocyclic quinuclidine derivatives 20a and 20b [43] were identified, and some of them proved to be effective in in vivo anti-inflammatory chronic pain models [44,45]. The study of ligands selective for the α7 receptor evidenced the presence of common pharmacophoric elements in the structures of most full-partial [20,21,25,4649] as well as silent agonists [36,3843], including a basic amine, a central group with hydrogen-bond acceptor properties and a lipophilic aryl moiety extending from the amine (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Since we had previously observed that the sulfonium compound, 1-ethyl-4-phenylthiomorpholin-1-ium trifluoromethanesulfonate [ 12 ], an analog of the diEPP silent agonists [ 21 ], behaved as a silent agonist of α7, inactive when applied alone but active when co-applied with an α7 PAM, we tested the sulfonium compounds in co-application with the type II PAM, 4-naphthalene-1-yl-3a,4,5,9b-tetrahydro-3- H -cyclopenta[c]quinoline-8-sulfonic acid amide (TQS) [ 22 ]. Compounds were co-applied at a concentration of 100 µM with 30 µM racemic TQS ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Two exemplar compounds termed as “silent agonists” for their tendency to desensitize α7 receptors with minimal channel activation are NS6740 and para-trifluoromethyl N , N -diethyl- N ′-phenylpiperazinium iodide ( p -CF 3 diEPP) compounds [ 11 ]. We recently reported synthesis and electrophysiological characterization of a new sulfonium analog of the diethyl- N ′-phenylpiperazinium scaffold,1-ethyl-4-phenylthiomorpholin-1-ium trifluoromethane sulfonate, in which the quaternary ammonium nitrogen atom is replaced with a sulfur [ 12 ]. This compound provides a charge isostere for the ammonium group, yet is not directly analogous given that in the diEPP compound the nitrogen bears two ethyl groups whereas the sulfonium analog has only one.…”
Section: Introductionmentioning
confidence: 99%